2019
DOI: 10.1080/21650349.2019.1618736
|View full text |Cite
|
Sign up to set email alerts
|

Testing ideation performance on a large set of designers: effects of analogical distance

Abstract: Testing ideation performance on a large set of designers: effects of analogical distance This paper reports an experiment that aims at providing new evidence to reinforce contradictory conclusions, as available in engineering design literature, on the effect of analogical distance on ideation performance of designers. The experiment involved 84 graduate students in Mechanical Engineering, with typical competencies on engineering design, but without any specific skill on analogy-based idea generation. The subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Advanced students have reported less obvious goals that result in more successful structural analogies [4], which may correlate with the type of documents they are looking for or with their search habits. In fact, novice designers benefit more from more specific sources of inspiration [26]. Furthermore, it has been shown that architecture students can develop this design by analogy ability, moving from literal similarity to analogical similarity [27].…”
Section: Architecture Information-seeking Behaviourmentioning
confidence: 99%
“…Advanced students have reported less obvious goals that result in more successful structural analogies [4], which may correlate with the type of documents they are looking for or with their search habits. In fact, novice designers benefit more from more specific sources of inspiration [26]. Furthermore, it has been shown that architecture students can develop this design by analogy ability, moving from literal similarity to analogical similarity [27].…”
Section: Architecture Information-seeking Behaviourmentioning
confidence: 99%
“…Authors such as Gonçalves et al (2016), Bonnardel and Marmèche (2004) and Ozkan and Dogan (2013) have worked on seeing how ideas from individual novice and experts differ in terms of their inspirations and analogical thinking while designing. Others have found that the stimuli related to near-field analogies are useful in generating ideas with higher novelty in the case of teams of nontrained designers who were graduate students (Jia et al, 2019). Most of the authors base their findings on results obtained from teams of students, who potentially behave differently than professionals (Chai, 2015).…”
Section: Creative Stimulation For Professionalsmentioning
confidence: 99%
“…For instance, their effects have been compared by distinguishing different facets of the contents the stimuli embedded. For instance textual vs graphical stimuli (Cardoso et al, 2012), function and context relatedness to the target design domain (Jia et al, 2019), word relatedness (Chiu and Shu, 2012) as well as solutions described in patents coming from "near" and "far" design domains when compared to the target domain (Fu et al, 2013). All the above-mentioned studies aimed at triggering some analogies by exposing the recipient to prior solutions and/or examples of ideas and concepts.…”
Section: Creative Stimuli Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogical relation is a typical thinking paradigm to associate concepts, and it is widely used in the ideation process (Gilon et al, 2018;Jia et al, 2020). "the Retriever" (Han et al, 2018) is a retrieval tool to present analogically related images or language terms.…”
Section: Ai-based Ideationmentioning
confidence: 99%